WACANA REKONSTRUKSI TURAS (TRADISI) ARAB Menurut Muhammad Abed al-Jabiri dan Hasan Hanafi - Dicky wirianto (Islam Futura, 2011)
This article focuses on Muhammad Abed al-Jabiri and Hasan Hanafi’s thought and their reactive attitude towards Moslem’s backwardness in many fields of life that they plan and design a mega project to address the causes of stagnation in the Moslem’s world. Al-Jabiri tries to reflect the formation of Arab reason as he thought that revival effort of Islam has deviated from its frames as the concequence it could not be able to face the western dominanance. In futher, he developed the basic principle and then he makes the reinterpretation with a format that has relevance to contemporarary values. While Hasan Hanafi tries to focus himself towards the “Tradition and Renewal” construction of Islam by creating a variety of methodologies, one of them is “The Axiom of Hermeunetic” wich applied to historical criticsm, eidetic criticsm and praxis critism. The important point this article is more about the effort of epistemology mapping in Arab world and effort to reinterpretrelligious teaching relevant to contemporary principles.